The current state of research on the two-way linkages between productivity and well-being - Andrew Sharpe; Shahrzad Mobasher Fard (International Labour Organization (ILO), 2022)
Interest in the topic of well-being has burgeoned in recent years as the weaknesses of gross domestic product (GDP) per capita as a proxy for well-being have become more apparent. At the same time, the global economy has experienced a productivity slowdown. Since productivity growth is recognized as being by far the most important long-term source of sustainable gains in living standards, this development has implications for the future of living standards around the world. These two developments raise a number of issues related to the two-way linkages between productivity and well-being. First, does slower productivity growth constitute a significant threat to the betterment of the well-being of the world's population, and, if so, by how much? Second, given that many indicators of well-being can have positive effects on productivity, should one aspect of any strategy to revive productivity growth be to focus on policies that improve well-being? The objective of this report is to survey the current state of research on the two-way linkages between productivity and well-being.
Keywords: 330; decent work; future of work; employment; quality of working life; productive development; productivity; Produktivität; Sozialer Indikator; Soziale Lage; Lebensqualität; Zufriedenheit; Gesundheit; Lohn; Theorie